Hairdo - Leyh, Genevieve (United States, 1998)
Film is a donation of the Margaret Mead Festival, supported by OSI-Budapest. Duration: 00:06:00 A celebration of beehives, falls, buns and twists- -the spectacular hairstyles of African-American women in neighborhood salons and on the streets of New Orleans. This is a study in what we do to ourselves to be ourselves and look beautiful.